The New Orleans Garden : Gardening in the Gulf South - Seidenberg, Charlotte (Book collections on Project MUSE., 1993)
Among America's garden cities, one of the most remarkably beautiful is New Orleans. Now the exotic New Orleans garden can live not only in romance but also in settings very close to home. Whether in the Vieux Carre or in the humid hinterlands, anyone hoping to recreate such a romantic spot in the climes of the Gulf Coast region should consult Charlotte Seidenberg's essential handbook.In this new edition of a favorite manual among New Orleans gardeners, Seidenberg instructs how to create a beautiful garden in this subtropical, sometimes richly alluvial zone and identifies plants that over gener.